6-Hydroxyhexyl 4-(E)-4-alkoxy/halostyryl)benzoates: synthesis, characterisation and study of mesomorphic and fluorescent properties. Issue 4 (16th March 2017) - Muhammad, Khushi; Hameed, Shahid; Siddiqi, Humaira M.; Eccher, Juliana; Bechtold, Ivan H.
ABSTRACT: Hydroxyhexyl esters of alkoxy and halostilbene carboxylic acids were prepared and studied for thermal, liquid crystalline and fluorescent properties. The decomposition temperatures were determined thermogravimetrically and the compounds were found stable at least up to 200°C. Differential scanning calorimetry (DSC) indicated two mesophases in alkoxystilbene caboxylates. The smectic nature of the liquid crystal (LC) compounds was identified from the optical textures and confirmed through X-ray diffraction (XRD) measurements, where SmA, SmB and CrE mesophases were observed. The compounds3a-g and3h-k show single absorption maxima in UV-visible spectra at around 338 and 322 nm, respectively. All the alkoxy compounds emit blue light in solution and in solid state in the wavelength range of 422–425 nm. GRAPHICAL ABSTRACT: